VD_FINDINFO ML / 2016 / 17 vom 13. Januar 2016 - VD Tribunal cantonal (2016)
RETRAITVOIE DE DROIT, COMMANDEMENT DE PAYER, NULLITÉ, ERREUR DE BASE, ERREUR ESSENTIELLE, DÉPENS | 23 CO, 24 CO, 69 LP, 106 al. 1 CPC (CH), 20 al. 2 TDC, 3 al. 2 TDC, 6 TDC